Complications Associated with the Use of Expandable Gases in Vitrectomy - Piotr Kanclerz; Andrzej Grzybowski (Journal of Ophthalmology)
Intraocular gases have been used in vitreoretinal surgery for over 40 years. The aim of this study was to review the complications related to the use of expandable gases in vitrectomy and their management. A PubMed, Cochrane Library, and Embase search was conducted using the terms “intraocular gas” and “vitrectomy for retinal detachment.” Of the articles retrieved by this method, all publications in English and abstracts of non-English publications were reviewed. Intraocular pressure elevation was reported in up to 58.9% patients after vitrectomy with expandable gas administration for retinal detachment. Vitreoretinal surgery is known to induce cataract development. With that, cataract progression is associated with lens exposure to intraocular gas, the duration of such exposure, patient’s age, and the magnitude of vitreous removal. With intraocular gas, the posterior surface of the lens becomes a strongly refractive factor, resulting in high myopia and temporary vision impairment. Other complications related to the use of expandable gases include anterior chamber and subconjunctival gas displacement. Single reports on subretinal and cranial gas migration were published. In vitrectomy for uncomplicated retinal detachments, attempts to shift from expandable gases towards air are observed. Nevertheless, gas tamponade remains a reasonable choice for patients suffering from retinal detachment.